Assessment tools of ageism – Literature review - Caklos, Milos; Kristová, Jarmila; Solárová, Martina (Magyar Gerontológia, 2024)
Ageism refers to stereotypes, prejudices and discriminatory expressions or attitudes towards older people. The World Health Organization defines ageism as a multidimensional, social phenomenon and considers it a public health problem.